Identity and attitude about the process of extinction of Quechua in the bilingual inhabitants of the district of Pontó (Ancash) - Pimentel Torres, Nicolás Tolentino (2021)
The present article, which derives from a master’s thesis in Linguistics carried out at the Universidad Nacional Mayor de San Marcos, aims to identify the relationship between the identity and attitude of the bilingual inhabitants of the district of Pontó, province of Huari, Ancash region, on the process of extinction of the Quechua language. Two questionnaires were applied to collect information on the identity and attitude towards their native language in people of different ages. The results obtained indicate that Quechua is generally spoken by the elderly, specifically in those over 60 years; consequently, it is threatened and dominated by the growing castellanization in the area of Pontó (Ancash), a similar aspect that occurs in most South American countries with respect to their native languages.